2012
DOI: 10.4103/0253-7613.96343
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antihiperlipidemic effect of Andrographis paniculata (Burm. f.) Nees and andrographolide in high-fructose-fat-fed rats

Abstract: Objectives:Andrographis paniculata (Burm. f.) Nees originates from India and grows widely in many areas in Southeast Asian countries. Andrographis paniculata (Burm. f.) Nees has shown an antidiabetic effect in type 1 DM rats. The present study investigates the purified extract of the plant and its active compound andrographolide for antidiabetic and antihyperlipidemic effects in high-fructose-fat-fed rats, a model of type 2 DM rats.Materials and Methods:Hyperglycemia in rats was induced by high-fructose-fat di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 12 publications
3
71
1
7
Order By: Relevance
“…Previous study was also investigated the effect of Phaseolus vulgaris in lowering blood glucose in diabetic rats 20 . Other study also showed the positive effect of Andrographis paniculata to reduce blood glucose in diabetic rats model as well 8 . Recent study enhanced these findings, however further study is needed to confirm possibility of adverse clinical effects.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous study was also investigated the effect of Phaseolus vulgaris in lowering blood glucose in diabetic rats 20 . Other study also showed the positive effect of Andrographis paniculata to reduce blood glucose in diabetic rats model as well 8 . Recent study enhanced these findings, however further study is needed to confirm possibility of adverse clinical effects.…”
Section: Discussionmentioning
confidence: 89%
“…In pre clinical trial, Andrographis paniculata Nees extract has the most effect for lower blood glucose in diabetic mice model 6 . The use of Momordica charantia extract was also reported to lower blood glucose in diabetic rat model as well as glibenclamide treatment as positive control 7,8 . Our previous study reported that mixture extract of Pterocarpus indicus 20%, Momordica charantia 10%, Phaseolus vulgaris 40% and Andrographis paniculata 30% showed significantly hypoglycemic effect on diabetic mice model 9 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Andrographolide is a diterpene lactone compound that most dominant, approximately 4% of the whole plant [9]. This andrographolide is an active compound as antidiabetes [11].…”
Section: Results and Analysismentioning
confidence: 99%
“…While STZ can be used to induce both types of diabetes (IDDM and NIDDM) with a toxic effect on the beta sel [18], [19]. In few studies [11], [19]- [22] that was included in this review, for induction the insulin resistance was using high fructose-fat fed. The insulin resistence occured due to the increase of fatty acid metabolism in the cells (intracellular) and resulting fatty acid CoA, diacylglycerol, and caramides.…”
Section: Mechanism Of Induction Of Diabetes In Ratsmentioning
confidence: 99%